Advances in euglenoid genomics: unravelling the fascinating biology of a complex clade - Fields, Oskar; Hammond, Michael J; Xu, Xiao; O'Neill, Ellis C (Trends in genetics, 2025)
Euglenids have long been studied due to their unique physiology and versatile metabolism, providing underpinnings for much of our understanding of photosynthesis and biochemistry, and a growing opportunity in biotechnology. Until recently there has been a lack of genetic studies due to their large and complex genomes, but recently new technologies have begun to unveil their genetic capabilities. Whilst much research has focused on the model organism Euglena gracilis, other members of the euglenids have now started to receive due attention. Currently only poor nuclear genome assemblies of E. gracilis and Rhabdomonas costata are available, but there are many more plastid genome sequences and an increasing number of transcriptomes. As more assemblies become available, there are great opportunities to understand the fundamental biology of these organisms and to exploit them for biotechnology.
Keywords: Euglena gracilis; Euglenida; genom protozoální; Genome, Protozoan; Genomics; Genome, Plastid; genomika; fylogeneze; genom plastidový; Phylogeny; Transcriptome; transkriptom